Bioenergy and emission characterizations of catalytic combustion and pyrolysis of litchi peels via TG-FTIR-MS and Py-GC/MS. (April 2020) - Liu, Chao; Liu, Jingyong; Evrendilek, Fatih; Xie, Wuming; Kuo, Jiahong; Buyukada, Musa
Abstract: This study characterized the catalytic combustions and emissions of litchi peels as a function of five catalysts as well as the effect of the best catalyst on the pyrolysis by-products. Na2 CO3 and K2 CO3 accelerated the devolatilization but delayed the coke burnout, while Al2 O3 enhanced the coke oxidation rate. Both comprehensive combustion index and average activation energy dropped with the added catalysts. CO2, CO, and H2 O were the main combustion gases between 300 and 510 °C. CO2, C-H, C=O, and C-O were generated from the pyrolysis between 200 and 430 °C above which CO2 and CH4 were slightly released. Total H2 O, CO2, CO, NO x and SO x emissions declined with the added catalysts among which K2 CO3 performed better. The main pyrolytic by-products at 330 °C were terpenoids and steroids (71.87%), phenols (15.51%), aliphates (9.95%), and small molecules (2.78%). At 500 °C, terpenoids and steroids (78.35%), and small molecules (3.20%) rose, whereas phenols (12.87%), and aliphates (5.83%) fell. Fatty acid, and ester decreased, while terpenoids, and steroids increased with MgCO3 at 330 °C. Litchi peels appeared to be a promising biowaste, with MgCO3 as the optimal catalytic option in terms of the bioenergy performance, and emission reduction. Graphical abstract: Image 1 Highlights: Litchi peels were characterized in terms of bioenergy generation and emission reduction. Na2 CO3 and K2 CO3 accelerated devolatilization and delayed char oxidation. MgCO3 minimized E α and performed better among the five catalysts. All catalysts reduced H2 O, CO2, NO x and SO x emissions during combustion. Terpenoids, steroids and phenols were the main pyrolysis products at 500 °C.